A new genus and species of Ichneumonini Latreille (Hymenoptera, Ichneumonidae, Ichneumoninae) from Oriental Region - Mao-Ling Sheng; Matthias Riedel; Zhong Wang (European Journal of Taxonomy, 2023)
Serratichneumon Riedel & Sheng gen. nov. and Serratichneumon maculatus Sheng & Riedel gen. et sp. nov. belonging to the tribe Ichneumonini of subfamily Ichneumoninae (Hymenoptera: Ichneumonidae), collected in the Oriental Region (China, Vietnam, and Indonesia), are described and illustrated. The new genus is placed in Tereshkin’s key to the Palaearctic genera of the subtribe Amblytelina, and compared with similar genera, Hepiopelmus Wesmael, 1845, and Tricholabus Thomson, 1894.